Benchmarking the GENE and GYRO codes through the relative roles of electromagnetic and E × B stabilization in JET high-performance discharges. (17th November 2016) - Bravenec, R; Citrin, J; Candy, J; Mantica, P; Görler, T
Abstract: Nonlinear gyrokinetic simulations using the GENE code have previously predicted a significant nonlinear enhanced electromagnetic stabilization in certain JET discharges with high neutral-beam power and low core magnetic shear (Citrin et al 2013 Phys. Rev. Lett . 111 155001, 2015 Plasma Phys. Control. Fusion 57 014032). This dominates over the impact of E   ×   B flow shear in these discharges. Furthermore, fast ions were shown to be a major contributor to the electromagnetic stabilization. These conclusions were based on results from the GENE gyrokinetic turbulence code. In this work we verify these results using the GYRO code. Comparing results (linear frequencies, eigenfunctions, and nonlinear fluxes) from different gyrokinetic codes as a means of verification (benchmarking) is only convincing if the codes agree for more than one discharge. Otherwise, agreement may simply be fortuitous. Therefore, we analyze three discharges, all with a carbon wall: a simplified, two-species, circular geometry case based on an actual JET discharge; an L-mode discharge with a significant fast-ion pressure fraction; and a low-triangularity high- β hybrid discharge. All discharges were analyzed at normalized toroidal flux coordinate ρ   =  0.33 where significant ion temperature peaking is observed. The GYRO simulations support the conclusion that electromagnetic stabilization is strong, and dominates E   ×   B shear stabilization.